2D → 3D corrugated structure self‐assembled from 4, 4′‐methylenebis(N‐(pyridin‐2‐ylmethylene)aniline and terephthalic acid: Crystal structure and selective anion separations via anion exchange. (15th May 2020) - Ghorbanloo, Massomeh; Saffari, Mitra; Asadi, Mina; Klopotowski, Maximilan; Janiak, Christoph; Morsali, Ali
Abstract : A new flexible cationic Zn(II)metal organic framework, [Zn 2 (BDC) 1.5 (L)(DMF)]NO 3 · DMF·solvent n, MOF 1, which is a corrugated two‐dimensional network, was synthesized by self‐assembly of Zn(NO3 )2 .6H2 O with 4, 4′‐methylenebis( N ‐(pyridin‐2‐ylmethylene)aniline as a neutral ligand and terephthalic acid in dimethyl formamide (DMF) as solvent and characterized by X‐ray diffraction. Because of the presence of uncoordinated nitrate (NO3 − ) ions in the channels, the compound was employed for ion‐exchange applications. We report a detailed study of the host–guest interaction for a cationic metal–organic framework (MOF) that can reversibly capture nitrate. The recrystallization of the MOF was evaluated by monitoring the anion exchange dynamics using a combination of powder X‐ray diffraction and Fourier transform infrared spectra with various kinds of foreign anions. This MOF showed fast and highly efficient Cr2 O7 2− and CrO4 2−, N3 −, MnO4 −, and SCN − exchange. The trapping capacities of Cr2 O7 2−, CrO4 2−, N3 −, MnO4 −, and SCN − were 105, 138, 44, 104, and 25mg/g at 25°C after 3h, respectively, and there was good recyclability for capturing N3 − and SCN − . [Zn 2 (BDC) 1.5 (L)(DMF)]NO 3 n exhibited anion exchange selectivity of SCN − in a solution containing a mixture of 0.025mmol N3 −, SCN −, CrO4 −2−, Cr2 O7 2−, and MnO4 − for 3h and exhibited anion exchange selectivity for SCN − and Cr2 O7 2− in a solution containing a mixture of 0.001mmol N3 −, SCN −, CrO4 2−, Cr2 O7 2−, and MnO4 − . Abstract : A corrugated two‐dimensional network of "six‐membered" [Zn2 (BDC)1.5 n rings of a new flexible cationic Zn(II) metal organic framework, [Zn 2 (BDC) 1.5 (L)(DMF)]NO 3 n, 1NO3, was synthesized by self‐assembly of Zn(NO3 )2 .6H2 O with 4, 4′‐methylenebis( N ‐(pyridin‐2‐ylmethylene)aniline as a neutral ligand and terephthalic acid in dimethyl formamide (DMF). This metal–organic framework showed fast and highly efficient Cr2 O7 2− and CrO4 2−, N3 −, MnO4 −, and SCN − exchange, and good recyclability for capturing N3 − and SCN − .